THE IMPORTANCE OF CORPORATE SOCIAL RESPONSIBILITY ON CONSUMER BEHAVIOUR IN MALAYSIA - Rahizah Abd Rahim,; Farah Waheeda Jalaludin,; Kasmah Tajuddin, (Asian Academy of Management Journal, 2011)
Malaysian consumers should now be more aware that corporations in pursuing their business objectives also have responsibility towards the society and the environment. The awareness level has increased through better level of education as well as the increased influence of media. Corporations also now believe that to a certain extent, their degree of involvement in corporate social responsibility (CSR) do have certain effect on consumers’ buying behaviour. This paper aims to examine the influence of CSR towards the buying behaviour of Malaysian consumers; whether they consider a corporation’s CSR initiatives before making any purchase decisions of the products and services. The definition of CSR was adopted from Carroll’s which included economic, legal, ethical and philanthropic responsibilities. A total of 220 structured questions were distributed with 193 returned for analysis. The results showed significant positive relationships between all the variables used in measuring CSR and consumer buying behaviour. Malaysian consumers’ priority however seemed to be different from Carroll’s pyramid where although economic responsibility remained the utmost priority, philanthropy stood second followed by ethical and legal responsibility.